An Interview with Roy Ellen - Nejm Benessaiah (Ethnobiology Letters, 2014)
I decided to undertake this interview with Professor Ellen, simply because I thought such a distinguished career deserved to be marked as he was retiring. Roy was happy to make time for our interviews, in the form of loosely structured conversation which, like the Arabian Nights, Roy pointed out, could have gone on forever, but I decided to draw the line at three sessions. Perhaps it could, and will go on to form part of a more in-depth biography, as I continued to discover other aspects and adventures of Roy’s interesting life in the course of other contexts, much as one does in the field. Much is known about what ethnobiologists and anthropologists say about another people’s lives; less is known about their own, apart from rare reflections, diaries and memoires. I found Roy’s reflections a source of comfort as I embarked on my own PhD fieldwork, reassuring me as I fumbled around, making my own unique but comparable mistakes among the insights I gleaned. The following is an edited version of the original interview. I hope it will be as enjoyable to the reader as it was to me working on it.